Analisis Lokasi Rawan Kecelakaan Pada Jalan Dengan Medan Datar Dan Bukit - Hadi, Suprapto; Wahyudi, S. Imam; Wibowo, Kartono; Oktopianto, Yogi; Eska Fahmadi, Aat; Widya Anggraeni, Inneke (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2025)
Accidents occur on various road terrains that cause drivers to experience losses from property to fatalities. Prof. Hamka Street and Siliwangi Street are located in the city of Semarang where Prof. Hamka Street is a road with a hilly topography while Siliwangi Street is a flat road. Problems occur on these road sections such as the many accidents that result in fatalities. The existing problems need to be addressed immediately so that they can reduce the risk of accidents in the future. The stages carried out first analyze the characteristics of accidents and vulnerable locations so that they know the most appropriate handling points and recommendations. In determining the location points prone to accidents using the EAN and UCL methods while in identifying the hazards of vulnerable locations using HIRARC. The results obtained on Prof. Hamka Street, the location points are at STA 6 (0 + 700) and 9 (1 + 000) while on Siliwangi Street, the location prone to accidents is at STA 18 (1 + 900) and 5 (0 + 600). The recommended handling is to repair the condition of the road surface that has cracks at the joints, signs at accident-prone locations that are still very lacking, street lighting at accident-prone locations, maintenance on the road so that obstacles on the side of the road do not block visibility and installation of vehicle speed control devices.